Kajian Biblika Wahyu 3:14-22 Tentang Jemaat Laodikia Dan Implikasinya Bagi Jemaat Kristen - Dawolo, Freddy Lans Deo (Kharisma: Jurnal Ilmiah Teologi, 2024)
The Church of Laodicea was described by Christ as a congregation that was neither hot nor cold, lukewarm, and arrogant because of its riches. Even though they are rich materially, they experience inconsistent faith and spiritual poverty, and are less aware of their need for God. Christ threatened to vomit them out if they persisted in this way of life. In today's materialistic world, it is easy for congregations to ignore spiritual needs. This brings problems to the growth of the congregation's faith. The research method uses biblical interpretation within the framework of verse-by-verse exegesis. The author also uses qualitative methods by collecting data from various articles and commentary books. The result of this research is that Christ as the head of the church rebukes inconsistent congregations, emphasizes spiritual riches as more important, and offers forgiveness for those who want to come to Him. There is a reward for those who obey until the end, namely the opportunity to feel the presence and glory of God. Jemaat Laodikia digambarkan oleh Kristus sebagai jemaat yang tidak panas dan tidak dingin, suam-suam kuku, dan sombong karena kekayaan. Meskipun kaya secara material, mengalami ketidakkonsistenan iman dan kemiskinan rohani, serta kurang menyadari kebutuhan akan Allah. Kristus mengancam akan memuntahkan apabila mempertahankan cara hidup demikian. Di dunia materialistik saat ini, mudah bagi jemaat mengabaikan kebutuhan rohani. Hal tersebut membawa masalah pada pertumbuhan iman jemaat. Metode penelitian menggunakan penafsiran biblika dalam bingkai eksegesis ayat per ayat. Penulis juga menggunakan metode kualitatif dengan menggumpulkan data dari berbagai artikel dan buku-buku commentary. Hasil dari penelitian ini adalah Kristus sebagai kepala gereja menegur jemaat yang tidak konsisten, menekankan kekayaan rohani lebih penting, dan menawarkan pengampunan bagi yang mau datang kepada-Nya. Ada upah bagi yang taat sampai akhir, yaitu kesempatan merasakan kehadiran dan kemuliaan Allah.